The Pol Pot regime : race, power, and genocide in Cambodia under the Khmer Rouge, 1975-79 - Kiernan, Ben. (New Haven : Yale University Press, 1996)
The Khmer Rouge revolution turned Cambodia into grisly killing fields, as the Pol Pot regime murdered or starved to death a million and a half of Cambodia's eight million inhabitants. This book - the first comprehensive study of the Pol Pot regime - describes the violent origins, social context, and course of the revolution, providing a new answer to the question of why a group of Cambodian intellectuals imposed genocide on their own country.
Introduction: The Making of the 1975 Khmer Rouge Victory -- Wiping the Slate Clean: The Regime Takes Shape -- Cleansing the Cities: The Quest for Total Power -- Cleansing the Countryside: Race, Power, and the Party, 1973-75 -- Cleansing the Frontiers: Neighbors, Friends, and Enemies, 1975-76 -- Writing on the Slate, 1975-77: The CPK Project -- An Indentured Agrarian State, 1975-77 (I): The Base Areas--The Southwest and the East -- An Indentured Agrarian State, 1975-77 (II): Peasants and Deportees in the Northwest -- Ethnic Cleansing: The CPK and Cambodia's Minorities, 1975-77 -- The Slate Crumbles, 1977-79: Convulsion and Destruction -- Power Politics, 1976-77 -- Foreign Relations, 1977-78: Warfare, Weapons, and Wildlife -- "Thunder without Rain": Race and Power in Cambodia, 1978 -- The End of the Pol Pot Regime.
Includes bibliographical references (pages 467-469) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Parti communiste du Kampuchea; Parti communiste du Kampuchea; Pol Pot -- 1928-1998; Rote Khmer; Pol Pot; Cambodia -- Politics and government -- 1975-1979.; Communism -- Cambodia; Political atrocities -- Cambodia; Genocide -- Cambodia; Cambodge -- Politique et gouvernement -- 1975-1979.; Atrocités politiques -- Cambodge; HISTORY; Communism; Genocide; Political atrocities; Politics and government; Cambodia; Kommunismus; Politik; Völkermord; Kambodscha; Rode Khmer; Revoluties; Massamoorden; Kambodscha; 1975-1979